In Memoriam Paul Moedikdo (1927-2016) Pakar Kriminologi Yang Berpendirian Tegas Sebuah Nekrologi Oleh Jan Van Olden - Reksodiputro, Mardjono, Prof. (Jurnal Hukum & Pembangunan, 2017)
Paul Moedikdo is just one of the many Indonesians who settled in the Netherlands because they were forced by circumstances resulting from the political upheaval in Indonesia in 1965 where there was an "unforgiving pursuit" of everything that smelled of leftism so that many intellectuals and activists were forced to seek happiness in the Netherlands. abroad, far from the homeland. Paul is an expert in criminology who works at the Willem Pompe Institute under the auspices of the University of Utrecht. As an Indonesian he is an ideal guest lecturer in efforts to improve the quality of education and research at the Faculty of Social Sciences in Jakarta. Paul Moedikdo Moeliono was born in Bandung on April 18, 1927 into a family of mixed Indonesian and Dutch intellectuals, where talent was well nurtured and academic achievement was considered something natural.